Drug‐related problems identified during medication review before and after the introduction of a clinical decision support system. (2nd October 2017) - Verdoorn, S.; Kwint, H.F.; Hoogland, P.; Gussekloo, J.; Bouvy, M.L.
Summary: What is known and objective: To facilitate the identification of drug‐related problems (DRPs) during medication review, several tools have been developed. Explicit criteria, like Beers criteria or STOPP (Screening Tool of Older Peoples' Prescriptions) and START (Screening Tool to Alert doctors to Right Treatment) criteria, can easily be integrated into a clinical decision support system (CDSS). The aim of this study was to investigate the effect of adding a CDSS to medication review software on identifying and solving DRPs in daily pharmacy practice. Methods: Pre‐ to post‐analysis of clinical medication reviews (CMRs) performed by 121 pharmacies in 2012 and 2013, before and after the introduction of CDSS into medication review software. Mean number of DRPs per patient, type of DRPs and their resolution rates were compared in the pharmacies pre‐ and post‐CDSS using paired t tests. Results and discussion: In total, 9151 DRPs were identified in 3100 patients pre‐CDSS and 15 268 DRPs were identified in 4303 patients post‐CDSS. The mean number of identified DRPs per patient (aggregated per pharmacy) was higher after the introduction of CDSS (3.2 vs 3.6 P < .01). The resolution rate was lower post‐CDSS (50% vs 44%; P < .01), which overall resulted in 1.6 resolved DRPs per patient in both groups ( P = .93). After the introduction of CDSS, 41% of DRPs were detected by the CDSS. The resolution rate of DRPs generated by CDSS was lower than of DRPs identified without the help of CDSS (29% vs 55%; P < .01). The two most prevalent DRP types were "Overtreatment" and "Suboptimal therapy" in both groups. The prevalence of "Overtreatment" was equal in both groups (mean DRPs per patient: 0.84 vs 0.77; P = .22), and "Suboptimal therapy" was more frequently identified post‐CDSS (mean DRPs per patient: 0.54 vs 1.1; P < .01). What is new and conclusion: The introduction of CDSS to medication review software generated additional DRPs with a lower resolution rate. Structural assessment including a patient interview elicited the most relevant DRPs. Further development of CDSS with more specific alerts is needed to be clinical relevant.